Socialization Website-Based Nursing Data Analysis Services at Banyumas Regional Hospital - Choiruna, Hasby Pri; Amalia, Reza Fajar; Pratama, Koernia Nanda; Setiono, Tulus; Ramadhan, Indah (Universitas Jenderal Soedirman, Jurusan Keperawatan, 2024)
Determining a nursing diagnosis is a very important part of being able to provide holistic and comprehensive nursing care for patients. Nursing diagnoses are determined based on the analysis of nursing data from the results of nursing assessments. Data analysis carried out manually has weaknesses, namely the precision and accuracy of the results, which are very dependent on the nurse's knowledge and experience in carrying out the nursing process. The process of manually analyzing nursing data also takes a relatively long time. Ramut Nursing Data Analysis (RNDA) is the first and free nursing data analysis service in Indonesia, which can help nurses, lecturers, and nursing students more easily, quickly, and accurately analyze nursing data and determine nursing diagnoses from the results of nursing assessments. Nurses at Banyumas Regional Hospital still carry out conventional nursing data analysis and are not yet familiar with the existence of RNDA services; Therefore, it is important to socialize the application of RNDA to analyze nursing data at Banyumas Regional Hospital. The activity was attended by 35 nurses with a series of activities including socialization of RNDA using the lecture method, demonstration of steps for using RNDA, discussion, and questions and answers, followed by nurses trying to practice using RNDA and providing feedback on RNDA. The results of the evaluation of this activity are that nurses understand more about nursing data analysis and RNDA, increase the speed of nurses in analyzing patient nursing data, increase the accuracy of identifying patient nursing diagnoses, increase the ease felt by Banyumas Regional Hospital nurses when patient analyzing nursing data, and providing positive feedback for RNDA.